Students’ satisfaction in learning the research subjects in the Lao language teacher’s System 12 + 4 Year 3 at Khangkhay Teacher Training College, academic year 2022-2023 - MALAYSAN, Pany (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research is about research "Students' satisfaction in learning the research course in the Lao language teacher's System 12 + 4 Year 3 at Khangkhay Teacher Training College, academic year 2022-2023". The aim is to study the level of satisfaction of students in learning research subjects in the Lao language teacher's Year 3 at Khangkhay Teacher Training College Overall and in each aspect, there are 4 aspects: Course content, Teaching and learning management, On the teacher's side and Environmental aspects. This study used a quantitative method, The sample group used in the study was 3 year Lao language students which has a total of 21 people, The instrument used in the research is a questionnaire, Statistics used for mean and standard deviation, data analysis is defined using data analysis results as follows: The satisfaction of the students of the Lao language teacher's course towards the study of research subjects in all aspects is very high which has a ( =3.86, SD=0.46). When separated according to the surface, it is expressed as: The content of the course as a whole and separated by items is at many levels with the average value ​( =4.10; SD=0.03). The teaching-learning management as a whole and separated by items are at many levels with the average value ​( =4.01; SD= 0.67). The teachers overall and separate according to the items are at many levels with the average value ​( =4.14; SD=0.69). The overall environmental aspect and separate items are at several levels with average values ​( =3.19; SD=0.43).